Spatial-Temporal Variations of the Intensity of Timber Resources Development in the Russian Far East from the Mid - 19th Century up to Now - Sheingauz, Alexander (Prostranstvennaâ ékonomica, 2006)
The volumes have been restored, by publications and archival data, of timber cutting in the Russian Far East in terms of present-day 10 subjects of the Russian Federation and 47 forest areas for 1850-2004. Five time periods have been singled out, by each of them total volumes of timber cutting and specific indices of cutting intensity have been calculated. For each period isolinear charts of cutting intensity have been constructed. Forest disturbance has also been considered, its dependence on the cutting intensity is confirmed by regression modelling